2014
DOI: 10.1177/0146167214539708
|View full text |Cite
|
Sign up to set email alerts
|

“Not One of Us”

Abstract: We investigated individual difference predictors of ascribing ingroup characteristics to negative and positive ambiguous targets. Studies 1 and 2 investigated events involving negative targets whose status as racial (Tsarnaev brothers) or national (Woolwich attackers) ingroup members remained ambiguous. Immediately following the attacks, we presented White Americans and British individuals with the suspects' images. Those higher in social dominance orientation (SDO) and right-wing authoritarianism (RWA)-concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 34 publications
7
21
0
Order By: Relevance
“…We found that relatively anti-egalitarian Whites were more likely to claim that a target's minority background had been formative when he was disreputable (vs. reputable). This accords with previous work in different but related domains, which has shown that individuals with higher levels of SDO are more likely to distance low status targets from dominant groups, thus maintaining the social stratification between groups at the top and those at the bottom that antiegalitarians favor (Ho et al, 2013;Ho, Kteily, & Chen, 2017;Kteily et al, 2014;Krosch et al, 2013). In contrast, we found that egalitarian Whites-who desire more equality between racial groups, despite their membership in an advantaged group-were more likely to give a biracial's minority background credit when that target was reputable than when he was disreputable.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that relatively anti-egalitarian Whites were more likely to claim that a target's minority background had been formative when he was disreputable (vs. reputable). This accords with previous work in different but related domains, which has shown that individuals with higher levels of SDO are more likely to distance low status targets from dominant groups, thus maintaining the social stratification between groups at the top and those at the bottom that antiegalitarians favor (Ho et al, 2013;Ho, Kteily, & Chen, 2017;Kteily et al, 2014;Krosch et al, 2013). In contrast, we found that egalitarian Whites-who desire more equality between racial groups, despite their membership in an advantaged group-were more likely to give a biracial's minority background credit when that target was reputable than when he was disreputable.…”
Section: Discussionsupporting
confidence: 91%
“…accentuated the tendency to see Black-White biracials as Black, consistent with the idea that they use hypodescent as a way of protecting the hierarchical racial order. Finally, Kteily, Cotterill, Sidanius, Sheehy-Skeffington, and Bergh (2014) directly manipulated the standing of an ambiguous target, and observed that higher SDO Whites perceived the same racially ambiguous target as looking less White upon learning he was low (vs. high) in status (Kteily et al, 2014, Study 3). By keeping low ranking targets out of advantaged groups, higher SDO individuals can maintain the status of groups at the top, consistent with their preferences for hierarchymaintenance.…”
Section: Blame?mentioning
confidence: 99%
“…Though some studies have focused on the outcomes of perceivers' categorization of multiracial targets in one particular way (i.e., in line with hypodescent-the tendency to categorize individuals with mixed racial ancestry into their socially subordinate group; Davis, 1991;Ho, Sidanius, Levin, & Banaji, 2011), much of this research has also revealed the flexibility and nuance of the racial categorization process more broadly. For example, studies have found that the same targets can be processed and categorized differently depending on perceivers' characteristics, such as their essentialist beliefs (e.g., Chao et al, 2013;Eberhardt, Dasgupta, & Banaszynski, 2003;Gaither et al, 2014), prejudice (e.g., Ho, Roberts, & Gelman, 2015;Hugenberg & Bodenhausen, 2004), hierarchy maintaining motives (Ho, Sidanius, Cuddy, & Banaji, 2013;Krosch, Berntsen, Amodio, Jost, & Van Bavel, 2013;Kteily, Cotterill, Sidanius, Sheehy-Skeffington, & Bergh, 2014), or racial identity (e.g., Gaither, Pauker, Slepian, & Sommers, 2016;Ho, Kteily, & Chen, 2017;Knowles & Peng, 2005). Studies reveal that target's characteristics, such as socioeconomic status (e.g., Young, Sanchez, & Wilton, 2015), racial identity of targets (e.g., multiple minority identities;…”
Section: Evidence For Flexibility In Categorizationmentioning
confidence: 99%
“…For instance, White people are more likely to racially profile individuals whose appearance is stereotypical of racial out-groups as potential terrorists . Moreover, the less White terrorist suspects look, the harsher treatment people tend to support (Kteily, Cotterill, Sidanius, Sheehy-Skeffington, & Bergh, 2014). Crucially, analyses of actual criminal-sentencing decisions show that the more ATTRIBUTING TERRORISM TO MENTAL ILLNESS 6 defendants' racial appearance differs from the dominant racial group, the harsher sentencing they receive (Blair, Judd, & Chapleau, 2004;Eberhardt, Davies, Purdie-Vaughns, & Johnson, 2006).…”
Section: Potential Consequences For Mental Representations and Percepmentioning
confidence: 99%